(untitled) (Delito y Sociedad, 2019)
One decade after the implementation of Law N° 13.298, and of its accessory one, Law N° 13.634, which creates the Jurisdiction of Youth Penal Responsibility in Buenos Aires province, it is certainly possible to analyse the configuration of the socio-cultural plot that structures the exercise of alternative measures to deprivation of liberty in Reference Center of Buenos Aires province since 2015. This article seeks to explore the cultural matrices which framed the institutional agents’, socio-community agents’ and you thunder criminal proceeding in progress around the categories of youth, liability and punishment. For that purpose, they were used depth-interview techniques, and it was analyzed that material from a cultural perspective of the «criminal issue».